Bioavailability of Nano-calcium from Parang Fishbone Extracted with Alkaline Solvent at Varying Ratio of NaOH and Extraction Time - Hayati, Febsi; Pranoto, Yudi; Triwitono, Priyanto (Indonesian Food and Nutrition Progress, 2025)
Calcium is an important nutrient that supports various biological functions of the body. Calcium plays a role in osmoregulation, muscle contraction, bone mineralization, blood clotting, and regulating the body's acid and base balance. Calcium absorption can be optimal in the body if it has a smaller particle size, namely nano-sized. Parang fish bones have great potential to be used as a source of calcium in the form of nano-calcium. Nano-calcium is calcium in the form of small particles, completely absorbed into the body, and can optimally meet the body's calcium needs. This research aims to evaluate the effect of variations in alkaline solvent concentration and extraction time on particle size and calcium levels of the resulting nano-calcium and determine the absorption of Parang fishbone nano-calcium in the in vitro bioavailability process of the inverted intestinal sac. The nano-calcium extraction method combines a sample ratio of NaOH at 1:3, 1:4, and 1:5 with extraction times of 30, 60, and 90 minutes. The in vitro reverse gut method tested the obtained nano-calcium for bioavailability. The concentration of the basic solvent and the optimum extraction time influence the nano-calcium produced due to the optimal contact time between the material and the solvent during the extraction process. Nano-calcium treatment with a sample ratio: NaOH of 1:4 with an extraction time of 60 minutes, resulted in a water content of 5.67%, ash content 74.20%; protein content 3.52%; fat content 0.117%; calcium content 35.46%; yield 44%, particle size 62 nm; and bioavailability at a 10 minute absorption time of 9.105%, a 20 minute absorption time of 9.222% and a 30 minute absorption time of 9.334%. The sample ratio treatment: NaOH 1:4 with an extraction time of 60 minutes is the best treatment because it can produce a smaller nano-calcium size and high bioavailability.